Nuevos registros de distribución del Águila Coronada (Harpyhaliaetus coronatus) en el oeste de Argentina - Gonnet, Jorge M. (1998)
The Crowned Eagle, Harpyhaliaetus coronatus, is regarded as endangered because of its low population numbers, the destruction of potential habitat, and the scarcity of records. Ecological studies on this species are required to develop conservation plans. We present 15 new distributional records obtained in the last 11 years. Based on the frequency of observed individuals and groups, and on the continuity of the habitats where it was recorded, we propose a priority area for ecological research on this species.